Pengaruh Manajerial Kepala Sekolah dan Supervisi Kepala Sekolah Melalui Disiplin Kerja sebagai Variabel Mediasi terhadap Kinerja Guru (Suatu Kajian Studi Literatur Manajemen Pendidikan) - Damianus Iku; Simon Sia Niha; Henny A. Manafe (Dinasti Review, 2022)
Abstract: Research that has a suitability will be useful for a literature review that reviews the influence of each variable or the impact on that variable. This research reviews the main literature review factors that have an impact on teacher performance, namely work discipline as an intervention variable, leadership or supervision of school principals, including teacher performance. The results obtained consist of: 1) Managerial principals have a positive and meaningful influence on work discipline; 2) Principal superintendents have a positive and meaningful influence on work discipline; 3) Managerial principals have a positive and significant influence on teacher performance; 4) Principal superintendents have a positive and significant influence on teacher performance; 5) Work discipline has a positive and significant impact on teacher performance; 6) Principal managerial or principal supervision simultaneously has an impact on teacher performance; 7) Work discipline is able to mediate managerial principals that influence teacher performance; 8) Work discipline can mediate to the supervision of the school principal which influences teacher performance. Abstrak: Riset yang memiliki kesesuaian akan bermanfaat untuk kajian pustaka yang mengkaji perihal pengaruh masing-masing variabel atau yang berimbas ke variabel tersebut. Riset ini mengulas perihal kajian pustaka faktor yang berdampak pada kinerja guru ialah disiplin kerja sebagai variabel intervening, kepemimpinan ataupun pengawasan kepala sekolah, termasuk kinerja guru. Hasil yang didapat terdiri atas: 1) Manajerial kepala sekolah memberi pengaruh positif dan bermakna pada disiplin kerja; 2) Supervisi kepala sekolah memberi pengaruh positif dan bermakna pada disiplin kerja; 3) Manajerial kepala Sekolah memberi pengaruh positif dan bermakna pada kinerja guru; 4) Supervisi kepala sekolah memberi pengaruh positif dan bermakna pada kinerja guru; 5) Disiplin kerja memberi pengaruh positif dan bermakna pada kinerja guru; 6) Manajerial kepala sekolah ataupun supervisi kepala sekolah secara simultan memberi dampak ke kinerja guru; 7) Disiplin kerja mampu memediasi pada manajerial kepala sekolah yang memberi pengaruh bagi kinerja guru; 8) Disiplin kerja dapat memediasi ke supervisi kepala sekolah yang memberi pengaruh pada kinerja guru.